Opinion of the Extension Personnel Regarding Different Aspects of Institutional Training Programmes - Kaur, Ravinder; Temesgen, Daniel; Kaur, Manmeet (Indian Journal of Extension Education, 2010)
Punjab is agriculturally progressive and a major contributor of national food reserve. To propel agriculture into 21st century, the quality, technical skill and management of agricultural manpower must improve inconsonance with the rapidly changing need of society both nationally as well as internationally. It was found that most of the extension personnel were satisfied with the contents covered in the training programmes, place of training and training shedule but were found dissatisfied with the theory-practical ratio, duration, selection of trainee and training notifications. Most of the respondents preferred lecture-cum-discussion method. The respondents were quite satisfied with the physical arrangements made in the training programmes. Training areas preferred by extension personnel were use and handling of audio-visual aids, training planning and implementation and subject matter technology.